The use of Allelic Expression Differences to Ascertain Functional Polymorphisms Acting in cis: Analysis of MMP1 Transcripts in Normal Lung Tissue - Heighway, J.; Bowers, N. L.; Smith, S.; Betticher, D. C.; Santibáñez Koref, M. F. (Annals of human genetics, 2005)
Summary Aberrant expression of matrix metalloproteinase 1 (MMP1) has been implicated in a number of pathological conditions of the lung. In vitro results and analysis of tumours and cell lines suggest that an insertion/deletion polymorphism at position ‐1607 in the promoter of the gene can influence expression levels. However, whether this polymorphism is associated with differences in expression in normal lung tissue remains to be established. Polymorphisms affecting expression in cis will lead to alleles with different expression levels and will result in unequal expression of both alleles in heterozygous individuals (allelic expression imbalance, AEI). This can be detected using a transcribed marker. Here we follow a new approach and use AEI to ascertain that the ‐1607 polymorphism is associated with allelic expression differences of MMP1 in normal lung tissue. This approach could be used to map the sites associated with inter‐individual expression differences in other genes. This is of particular interest since such sites allow prediction of expression levels, and can be used to test whether genetically determined differences in expression influence inter‐individual differences of a phenotype of interest, such as disease predisposition.